PENGGUNAAN MEDIA AUDIO UNTUK MENINGKATKAN KEMAMPUAN MENYIMAK DONGENG ANAK PADA SISWA KELAS IV SEKOLAH DASAR - Heny Kusuma Widyaningrum (Universitas PGRI Madiun, 2015)
In elementary school, attentiveness is an important language skill. On the other hand, thefact shows that the lesson of attentiveness still low ang students' interest is poor. Thus, theuse of proper media can be considered in order to make lessons' goal of attentive skill isapproachable. Based on the above reason, this research purposes to improve attentiveskill in myth in fourth grade students in SDN Sambirejo 1 Madiun by using audio media,that is myth recording. This research uses Classroom Action Research consist of twocycles. The result research shows the improvement on dispute the characters and thescene. Lessons' process is in these aspects: attention, seriousness, and activeness areimprove up to 11,8%. Result of improvement of attentive skill in myth in aspectcharacters and scene in the first cycle and second cycle are improve in average of 17,3%and7,4%.